Are We Protecting Our History? A Municipal-Scale Analysis of Historic Preservation, Flood Hazards, and Planning - Rumbach, Andrew; Bierbrauer, Anna; Follingstad, Gretel (Journal of planning education and research, 2024)
Historic resources are important community assets that may be at risk from natural hazards, but few studies examine their risk or protection. We map the location of historic resources in municipal areas in Colorado (n = 863) and find that 16.8 percent of National Register and State Register properties (n = 145) intersect with a mapped floodplain, as well as 74.0 percent of National Register districts. We then study fourteen case study municipalities that are representative of those with substantial shares of their historic resources in floodplains. We find that most municipalities value their historic resources but very few proactively plan for their protection from hazards.